The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/10495398.2017.1279169
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pig as a Model for Mesenchymal Stem Cell Therapies for Bone Regeneration

Abstract: Bone is a plastic tissue with a large healing capability. However, extensive bone loss due to disease or trauma requires extreme therapy such as bone grafting or tissue-engineering applications. Presently, bone grafting is the gold standard for bone repair, but presents serious limitations including donor site morbidity, rejection, and limited tissue regeneration. The use of stem cells appears to be a means to overcome such limitations. Bone marrow mesenchymal stem cells (BMSC) have been the choice thus far fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 140 publications
0
29
0
Order By: Relevance
“…In previous investigations, it has been found that the combination of stem cell transplantation with other therapeutic methods could affect the efficiency of stem cell transplantation [45-48]. On the other hand, BMSCs transplantation has been revealed as a promising strategy for ONFH treatment; however, only patients with medium-size lesions could benefit from its application [15, 16]. The findings of other studies suggested that the treatment with SC-79 (an Akt activator) and Vitamin K2 significantly improved the efficacy of osteogenesis in animals [17, 21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous investigations, it has been found that the combination of stem cell transplantation with other therapeutic methods could affect the efficiency of stem cell transplantation [45-48]. On the other hand, BMSCs transplantation has been revealed as a promising strategy for ONFH treatment; however, only patients with medium-size lesions could benefit from its application [15, 16]. The findings of other studies suggested that the treatment with SC-79 (an Akt activator) and Vitamin K2 significantly improved the efficacy of osteogenesis in animals [17, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical study suggested that bone healing after autologous BMSCs treatment for ONFH begins two weeks after the transplantation, and complete healing is achieved after nine weeks [15]. A five-year follow-up study revealed that the combination of implantation of autologous bone marrow cells and auto-iliac cancellous bone grafts generated comparable clinical results with those of head-preserving procedures in medium-sized lesions [16], indicating that BMSCs implantation is promising for ONFH treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Pigs are some of the most attractive and relevant large animal models for preclinical studies since their size, anatomy, genomic organization, and physiology are very similar to humans. 7,9,36 In a porcine preclinical model, the autologous transplantation of pASCs avoids triggering an adverse immune response.…”
Section: Applications In Preclinical Modelsmentioning
confidence: 99%
“…Pigs have been used to investigate innovative pASCs bone regeneration strategies. 36 The osteogenic differentiation of pASCs is a well-known process. 23,37,38 Several studies combined pASCs differentiated into osteocytes with various types of scaffold such as hydroxyapatite, 22 polycaprolactone, 39 or oligo (polyethylene glycol) fumarate (OPF) hydrogel 40 to repair osteochondral defects.…”
Section: Applications In Preclinical Modelsmentioning
confidence: 99%
“…Previous studies in large animals have shown massive bone defects regenerate well after implantation of tissue‐engineering bone (TEB, Viateau, Guillemin, & Bousson, ). Although bone defect models are well established in large animals, their production costs are high and intensive nursing is required; additionally, a long time is required for sample processing, which limited the suitable methods for sample evaluation (Rubessa et al, ). Moreover, the precise cellular and molecular mechanisms of bone repair are difficult to dissect.…”
Section: Introductionmentioning
confidence: 99%